1996
DOI: 10.3354/ame011151
|View full text |Cite
|
Sign up to set email alerts
|

Does ambient UV-B radiation influence marine diatom-dominated microbial mats? A case study

Abstract: Intact natural microbial mats collected from a shallow microtidal bay were incubated in the presence or absence of ambient ultraviolet-B radiation (UVBR) in an outdoor flow-through system for 2 and 6 wk, respectively. The microbial mats were cohesive and dominated by a large, motile diatom species, Gyrosigma balticum (Ehrenberg) Rabenhorst. The variables studied included biomass, composition of microalgae and meiofauna, bacterial biomass, pigment composition and presence of UV-absorbing compounds. Carbon assim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Many studies have demonstrated that grazers are unaffected by UVR exposure (DeNicola & Hoagland 1996, Sundbäck et al 1996b, Hill et al 1997, Vinebrooke & Leavitt 1999. Our study agrees with these earlier experiments since we did not find any significant pattern of treatment effect on meiofauna, neither on nematode nor on ontogenic stages of harpacticoid copepod abundances.…”
Section: Treatment Effectssupporting
confidence: 93%
See 1 more Smart Citation
“…Many studies have demonstrated that grazers are unaffected by UVR exposure (DeNicola & Hoagland 1996, Sundbäck et al 1996b, Hill et al 1997, Vinebrooke & Leavitt 1999. Our study agrees with these earlier experiments since we did not find any significant pattern of treatment effect on meiofauna, neither on nematode nor on ontogenic stages of harpacticoid copepod abundances.…”
Section: Treatment Effectssupporting
confidence: 93%
“…Benthic microalgae can avoid UVR fluxes by migrating downward in the sediment since vertical migration offers substantial protection for cyanobacteria against UVR exposure (Nadeau et al 1999). Although this behavioral process probably applies for diatoms (Sundbäck et al 1996b), its longterm efficiency is doubtful ). Attenuation of UVR-induced impairments can also be achieved through the synthesis of various cellular com-ponents absorbing in the UVR band.…”
Section: Attenuation Of Uvr Damagementioning
confidence: 99%
“…Comparable densities of phytoflagellates in shallow intertidal sediments have been recorded previously (e.g. Sundba¨ck et al, 1996;Hoppenrath, 2000;Lee & Patterson, 2002).…”
Section: à2mentioning
confidence: 66%
“…Whitton & Potts, 2000). Vertical migration may perhaps be an additional strategy, providing an immediate response to PAR (Thajuddin & Subramanian, 2005) and UVR (Sundba¨ck et al, 1996;.…”
Section: à2mentioning
confidence: 99%
“…These include damage to nuclear DNA (dimes formation, Karentz et al 1991a, Buma et al 1995 with consequent inhibition of cell growth rates, inhibition of photosynthesis with lesions in the Photosystem 11-D1 reaction centre protein (Jordan et al 1991), loss of, and changes to, the key photosynthetic enzyme, ribulose bis-phosphate carboxylase (Rubisco) (Strid et al 1990, Lesser et al 1994, Wilson et al 1995, Lesser 1996, decreased nitrogen uptake, metabolism and protein synthesis (Dohler et al 1987, Goes et al 1995, Dohler 1996, and loss of photo-orientation and motility in dinoflagellates, diatoms and other species (e.g. Hader & Hader 1988, Ekelund 1990, Donkor et al 1993, Nielsen & Ekelund 1993, Sundback et al 1996. The severity of these effects depends on the length and intensity of UVB exposure, the nutrient status of the cells, individual species responses, and supplementary radiation involved in repair processes (e.g.…”
Section: Introductionmentioning
confidence: 99%